ANALYSIS OF THE ACHIEVEMENT OF STOPPING OPEN DEFECATION (BABS) IN URBAN AND COASTAL AREAS IN MEDAN CITY - Nanda, Meutia; Nayla, Imsakina; Nasution, Rianda Fadila; Mutiara, Yusnidar Sari; Lea, Salshabilla April; Nasution, Linda Liswana; Zahra, Nurul (HEARTY, 2026)
Achievement of Stop Open Defecation (BABS), as the first pillar of Community-Based Total Sanitation (STBM), in coastal and urban areas of Medan City. Stop BABS is a key indicator of the success of the STBM program in achieving Open Defecation Free (ODF) status in villages/sub-districts. This study aims to analyze the achievement of Stop BABS in Medan City, namely urban and coastal areas. The problems encountered in the Stop BABS study are Behavioral issues, Facilities and Infrastructure and Equipment (no proper and safe septic tank suction equipment). This study uses a qualitative method with a descriptive analysis approach. Secondary data was collected from the Medan City Health Office through the STBM progress report for the third quarter of 2025. The results showed a disparity between sanitation achievements from Stop Defecation in urban and coastal areas. Issues encountered in the Stop Defecation study included behavioral issues, facilities, infrastructure, and equipment. Urban areas achieved a Stop Defecation rate of 96.42%, exceeding the national target of 80%. However, coastal areas only achieved 70%, with Belawan and Sicanang Villages still at 0% in Stop Defecation achievement. Conclusion: The disparity in achievement between regions indicates the need for more intensive interventions in coastal areas, particularly in providing basic sanitation facilities and increasing public awareness.